Pertuzumab, trastuzumab and taxane-based treatment for visceral organ metastatic, trastuzumab-naive breast cancer: real-life practice outcomes - KÖSTEK, OSMAN; YUMUK, PERRAN FULDEN (SPRINGER, 2019)
PurposeIn this study, we aimed to describe the real-life practice outcomes of pertuzumab-trastuzumab-taxane (PTT) combination in visceral organ metastatic, trastuzumab-naive breast cancer (BC) patients.MethodsThis study was conducted by Turkish Oncology Group and included 317 patients' data from 36 centers.ResultsMedian age was 51 (22-82). Median PFS was 28.5months, while median OS was 40.3months. Patients with brain metastases (n: 13, 4.1%) had worse PFS (16.8m vs. 28.5m; p=0.002) and OS (26.7m vs. 40.3m; p=0.009). Patients older than 65years of age (n: 42, 13.2%) had significantly lower OS results (19.8m vs. 40.3m; p=0.01). Two hundred sixty-eight patients (86.7%) received docetaxel while 37 patients (11.7%) received paclitaxel. PFS and OS were similar between taxane groups. In eight patients (2.5%), 5-40% ejection fraction decrement from baseline was detected without any clinical sign of heart failure.ConclusionsOur RLP trial included only visceral metastatic, trastuzumab-naive BC patients including cases with brain involvement who received PTT combination in the first-line treatment. Regardless of negative prognostic characteristics, our results are in parallel with pivotal trial. Further strategies for brain metastasis should be developed to improve outcomes despite encouraging results with PTT treatment. Taxane selection can be personalized and endocrine maintenance may further improve outcomes after taxanes were discontinued. To our knowledge, this is the largest scale real-life clinical practice study of pertuzumab-trastuzumab-taxane therapy to date.
Keywords: Pertuzumab; Trastuzumab; AntiHER2; Visceral metastasis; Brain metastasis; CLINICAL-PRACTICE; OLDER PATIENTS; TRIAL; DOCETAXEL; SURVIVAL; PLUS; CHEMOTHERAPY; PACLITAXEL; THERAPY